New spectral image compression method based on an optimal phase coding and the RMS duration principle - Alfalou, A.; Elbouz, M.; Mansour, Ali; Keryer, G. (Institute of Physics, 2010)
By using only phase information, this paper describes a new spectral lossy compression method which can: reduce required memories; adaptively retrieve original images by using only spectral phase information; increase the peak-to-correlation energy (PCE) at the output of the correlator; and be easily employed in major encryption techniques. To increase the compression ratio of the proposed method, an optimal phase coding based on 'a fading grid' is performed. In fact, a variable number of quantization bits has been used to quantize phase information depending on the importance of the spectral phases. The phase information could be classified according to the concept of 'RMS duration'. Many simulations have been carried out. Our experimental results corroborate the performance of the proposed new method.